Strengthening the Role of Women in Preventive against Covid-19 Efforts in Kampung Tenun, Topa Village, Baubau: Penguatan Peran Perempuan dalam Upaya Preventif Covid-19 di Kampung Tenun Desa Topa, Baubau - Wa Ode Nesya Jeni Samrida; Minarti Minarti; Syastriani Isna Putri Syarif (Poltekkes Kemenkes Palu, 2022)
Introduction: The spread of the COVID-19 virus is increasing, especially in Kampung Tenun, Topa Village, Baubau. Women take a big role in ensuring the health of the family. All information that is a source of improving family health becomes part of the role of women as wives, mothers and children. The purpose of this activity is to ensure that women have the correct information about COVID-19 so that their families are well educated and healthy during the pandemic. Methods: The implementation of the activity uses the community participation method with indicators of community participation in activities, namely first through counseling about covid-19 and how to prevent it, a dissertation on pre-posttest evaluation, hand washing practices and fitness exercise activities for 60 minutes with an instructor. participants totaled 30 people. The results of the counseling activity showed that after receiving counseling related to Covid-19 prevention, there was an increase in the knowledge of the women of the Topa Village Weaving Village, being able to practice good and correct hand washing and enthusiastically participating in counseling activities. fitness training hopes to become a resident's routine. We hope that activities involving women must be sustainable because women's role is very large for health starting at home (family).